Ultrafast Photodissociation Dynamics of $n$-Butyl Iodide in the A-Band (Journal of Atomic and Molecular Sciences, 2021)
Ultrafast photodissociation dynamics of n-butyl iodide in the $A$-band has been studied by femtosecond time-resolved mass spectroscopy coupled with ion imaging. The time constant of $n$-$C_4H_9I$ in the A-band with one photon excitation at ~267 nm is measured to be ~(58$±$6) fs. The ion images of $I (^2P_{3/2})$ and $I^* (^2P_{1/2})$ at ~267 nm and ~274 nm are obtained and analyzed to yield corresponding speed and angular distributions. The dependences of dissociation mechanism on excitation wavelength and the size of the alkyl radical are discussed.